Positive Politeness In “On the Basis of Sex” Movie - Aloyna Misje Perarihenta Karo-Karo; Elia Masa Gintings (TRANSFORM : Journal of English Language Teaching and Learning, 2021)
This study aimed at analyzing the types of positive politeness strategy of the main character which represented in On the Basis of Sex movie. The descriptive qualitative method used to gain the findings of the data. The video recording used to gain transcription from the movie was the source of the data. From that findings, the data found were 90 utterances spoken by Ruth as the main character of the movie. And from those utterances, 29 represented as Positive Politeness which was 32,2%. The forms of positive politeness, Ruth represented 27 forms of positive politeness, with Question was the most dominant type of all with 8 amounts (29%), followed by Request 7 (26%), Disagreement with 6 (22%), Suggestion with 4 (15%) amount, and Rejection and Chasetisement shared 1 (4%). Thus, the writer found that positive politeness in the movie often emerged because the theme was about law school, court room, and national administration.